Ca(v)1.4α1 Subunits Can Form Slowly Inactivating Dihydropyridine-Sensitive L-Type Ca(2+) Channels Lacking Ca(2+)-Dependent Inactivation - Koschak, Alexandra (J Neurosci, 2003)
The neuronal L-type calcium channels (LTCCs) Ca(v)1.2α1 and Ca(v)1.3α1 are functionally distinct. Ca(v)1.3α1 activates at lower voltages and inactivates more slowly than Ca(v)1.2α1, making it suitable to support sustained L-type Ca(2+) inward currents (I(Ca,L)) and serve in pacemaker functions. We compared the biophysical and pharmacological properties of human retinal Ca(v)1.4α1 using the whole-cell patch-clamp technique after heterologous expression in tsA-201 cells with other L-type α1 subunits. Ca(v)1.4α1-mediated inward Ba(2+) currents (I(Ba)) required the coexpression of α2δ1 and β3 or β2a subunits and were detected in a lower proportion of transfected cells than Ca(v)1.3α1. I(Ba) activated at more negative voltages (5% activation threshold; -39mV; 15 mm Ba(2+)) than Ca(v)1.2α1 and slightly more positive than Ca(v)1.3α1. Voltage-dependent inactivation of I(Ba) was slower than for Ca(v)1.2α1 and Ca(v)1.3α1(∼50% inactivation after 5 sec; α2δ1 + β3 coexpression). Inactivation was not increased with Ca(2+) as the charge carrier, indicating the absence of Ca(2+)-dependent inactivation. Ca(v)1.4α1 exhibited voltage-dependent, G-protein-independent facilitation by strong depolarizing pulses. The dihydropyridine (DHP)-antagonist isradipine blocked Ca(v)1.4α1 with ∼15-fold lower sensitivity than Ca(v)1.2α1 and in a voltage-dependent manner. Strong stimulation by the DHP BayK 8644 was found despite the substitution of an otherwise L-type channel-specific tyrosine residue in position 1414 (repeat IVS6) by a phenylalanine. Ca(v)1.4α1 + α2δ1 + β channel complexes can form LTCCs with intermediate DHP antagonist sensitivity lacking Ca(2+)-dependent inactivation. Their biophysical properties should enable them to contribute to sustained I(Ca,L) at negative potentials, such as required for tonic neurotransmitter release in sensory cells and plateau potentials in spiking neurons.